Industry 4.0 and Regional Transformations - De Propris, Lisa; Bailey, David (Taylor & Francis, 2020)
This volume brings together expert contributors to explore opportunities and challenges that Industry 4.0 is likely to pose for regions, firms and jobs in Europe. Drawing on theory and empirical cases, it considers emerging issues like servitization, new innovation models for local production systems, and the increase in reshoring.